Analisis Sistem Kerja Purchasing Terhadap Pengadaan Bahan Makanan Kitchen Di Cambridge Hotel Medan - Lesmana, Bayu; Tondang, Bahagia; Syahrul, Syahrul (Politeknik Pariwisata Medan, 2023)
This study aims to (1) analyze the process of improving the quality of purchasing work for the procurement of food ingredients at the Cambridge Hotel Medan. (2) find out the implementation of the food procurement system in the purchasing department of the Cambridge Hotel Medan after improving the quality of the work system. This research was conducted using qualitative research methods by conducting interviews and the sample used in this study was the Purchasing Department Head. The author conducts interviews with purchasing staff and then the results of the answers are processed. The results of the research show that a). In the process of receiving food ingredients, the receiving party carries out a physical examination (physical check) of the food ingredients to ensure compliance with the specifications and quality of the food ingredients, although sometimes the receiving party itself is not consistent with receiving food ingredients that do not comply with the specifications ordered during the food ingredients. can still be processed by the user. b). In the process of signing a food procurement contract with a supplier, the purchasing party always compares market prices with those proposed by suppliers. The coordination model that has been running so far has been quite effective where both parties always use WhatsApp social media.